Comparative Genre Analysis of Research Article Abstracts in More and Less Prestigious Journals: Linguistics Journals in Focus - El-Dakhs, Dina Abdel Salam (Research in Language, 2018)
The current study compares the rhetorical structure and metadiscourse of research article abstracts in more and less prestigious journals in Linguistics. To this end, 200 abstracts from peer-reviewed Linguistics journals that are indexed in the Web of Science and Scopus were compared with 200 abstracts extracted from peer-reviewed Linguistics journals that are not indexed in either of these two highly ranked databases. Using Hyland’s (2000) model of move analysis and Hyland’s (2005) taxonomy of metadiscourse, the study reveals that abstracts in less prestigious journals typically include longer moves for introduction, purpose and method while abstracts in more prestigious journals include significantly lengthier findings. As for metadiscourse, abstracts in less prestigious journals employ significantly more transitions, frame markers and evidentials whereas the abstracts in more prestigious journals exhibit a higher use of code glosses, hedges, boosters and self-mentions. The results are interpreted with reference to the types of journals, and pedagogical implications and new research directions are proposed.